Antimycobacterial activity and Immunogenic profiles of selected Mangrove plants from Sulaman wetland in Sabah against mycobacterium tuberculosis - Tamar Kansil (2023)
The high tuberculosis mortality rate has piqued the interest of researchers and prompted efforts to address this public health issues. Social deprivation, contributing to the high incidence of tuberculosis (TB) cases, remains a significant threat in the state of Sabah, particularly considering the emergence of Mycobacterium tuberculosis drug resistance, which is not well understood. On the other hand, mangrove species have exhibited remarkable compounds with medicinal significance, including antimicrobial activity that has the potential to induce immunomodulating effects. This study aimed to assess the potential antimycobacterial activity of plant extracts in both treatment and pre-treatment approaches. The study analyzed the effects of these extracts on the expression profiles of immunogenic genes in mice infected with M. tuberculosis strain SBH257, which is a clinical strain from Sabah. Initially, 26 samples were collected from different parts of six mangrove plant species (Avicennia marina, Bruguiera gymnorrhiza, Ceriops tagal , Rhizophora apiculata, Rhizophora mucronata and Xylocarpus granatum) in Sulaman Lake Mangrove Forest, Tuaran, Sabah. Hexane and ethyl acetate extracts were obtained and analyzed for their total phenolic content (TPC) and their ability to scavenge DPPH free radicals via Folin- Ciocalteu’s and 1,1-diphenyl-2-picrylhydrazyl (DPPH) assays, respectively. The antimycobacterial activity of the extracts was then evaluated using broth microdilutions and the microtiter resazurin assay at concentration ranges from 0.02 mg/mL to 10 mg/mL. The extract with the highest inhibition strength and the lowest MIC value was selected for the in vivo study. In the animal study, acute and subacute toxicity tests were conducted following the OECD guidelines 423 using male and female BALB/c mice aged 8 – 10 weeks to assess the safety of the extracts. In the acute oral toxicity test, a single dose of 2000 mg/kg body weight of the tested extract was administered orally to the mice. For the sub-acute toxicity test, the extract was administered daily at doses of 200 mg/kg and 300 mg/kg body weight for up to 28 days in different treatment groups. The mice were closely observed for any signs of toxicity. Vital organs and blood samples were collected from the mice to analyze relative organ weight, kidney function, and liver function. To further evaluate the immunomodulatory effects of the extract, the expression of different immune related genes involved in the innate and adaptive responses of TB-infected mice against plant extracts was analyzed using RT-qPCR. Tuberculosis infection was induced in the mice through intranasal challenge with a M. tuberculosis suspension. The extracts were administered orally for two weeks, starting 14 days post-infection at a selected dose of 200 mg/kg. Moreover, the mice were pre-treated with the extract for 14 days prior to the MTB infection. Mice were divided into five groups, each consisting of 6 animals. Lung tissues were harvested from the mice, and total RNA was extracted for gene expression analysis. Furthermore, the gene expression of the MTB virulence genes, IS6110 and MPB64, was quantified in each group. Interestingly, the results revealed that all the tested extracts demonstrated antimycobacterial activity via resazurin assay. The ethyl acetate extract of Ceriops tagal leaf exhibited the highest antimycobacterial activity, with a minimum inhibitory concentration (MIC) value of 0.039 mg/ml. On the other hand, the hexane extracts of R. apiculata root and R. mucronata stem displayed the lowest antimycobacterial activity, with a MIC of 2.5 mg/ml. Among the extracts, the ethyl acetate extracts of Ceriops tagal leaf were among the higher total phenolic content (129.59 mg GAE/g) and antioxidant activity (778.89 μg/mL). These findings suggest that the phenolic compounds present in the extracts may be responsible for the antimycobacterial activity observed. Furthermore, the acute and sub-acute in vivo toxicity tests showed no observable symptoms of toxicity present with 100 % survival rate among the mice. Additionally, there were no significant changes in body weight compared to the control group. It is noteworthy that the interferon gamma (IFN-γ) gene, which plays a crucial role in protective immunity against MTB, showed a significant upregulation in the lungs of MTB-infected mice compared to healthy mice. However, the ethyl acetate extract of Ceriops tagal leaf remarkably suppressed IFN-γ production in both the treatment and protective groups, comparable to the rifampicin group. This demonstrates a potent immunomodulatory potential at a dosage of 200 mg/kg. The results align with the expression levels of other innate immune genes (IL2, CLEC4E, CLEC7A) and adaptive immune genes (LY6I, IFN-γ, and TNF-α) in the treatment group, which exhibited significant upregulation. Furthermore, the innate immune genes (IL2, CLEC4E, CLEC7A, and MMP9) and adaptive immune genes (LY6I, IFN-γ, TNF-α, and FCRG1) displayed significant downregulation in the protective group. These findings suggest that the ethyl acetate extract of Ceriops tagal leaf exerted a substantial immunomodulatory activity, enhancing protection in the lungs of MTBinfected mice. Additionally, the downregulation of MTB virulence genes (IS6110 and MPB64) further supports these results, indicating that the daily treatment and pretreatment of mice with the extract led to bactericidal action against MTB comparable to the effect of rifampicin. In summary, these findings provide a platform for future identification of phytoconstituents that contribute to the antimycobacterial activity of the ethyl acetate extracts of Ceriops tagal leaf, as well as for conducting pre-clinical studies. The discovery of potential compounds with anti-tubercular activity from these extracts could facilitate the development of novel drugs to combat tuberculosis.